2018
DOI: 10.1002/2017wr022042
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic Controls on Floodplain Soil Organic Carbon in the Yukon Flats, Interior Alaska, From Reach to River Basin Scales

Abstract: Floodplains accumulate and store organic carbon (OC) and release OC to rivers, but studies of floodplain soil OC come from small rivers or small spatial extents on larger rivers in temperate latitudes. Warming climate is causing substantial change in geomorphic process and OC fluxes in high latitude rivers. We investigate geomorphic controls on floodplain soil OC concentrations in active‐layer mineral sediment in the Yukon Flats, interior Alaska. We characterize OC along the Yukon River and four tributaries in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 81 publications
(165 reference statements)
3
62
0
Order By: Relevance
“…The total carbon stock increases by approximately 40-360% across individual study river floodplains when estimating stocks using field data (Figure 3). Samples taken horizontally into cut banks ranged from 1 to 4.2 m below the top of the bank, and the OC concentrations of these samples were similar to the OC concentrations of mineral sediment within the top 1 m (median = 2.1% OC from cut banks compared to median = 2.2% OC in mineral sediment within top 1 m; Lininger et al, 2018). In contrast, previous comparisons with NCSCD have found that the NCSCD may overestimate stocks in some areas (Zubrzycki et al, 2013).…”
Section: Carbon Stocks In the Yfmentioning
confidence: 61%
See 2 more Smart Citations
“…The total carbon stock increases by approximately 40-360% across individual study river floodplains when estimating stocks using field data (Figure 3). Samples taken horizontally into cut banks ranged from 1 to 4.2 m below the top of the bank, and the OC concentrations of these samples were similar to the OC concentrations of mineral sediment within the top 1 m (median = 2.1% OC from cut banks compared to median = 2.2% OC in mineral sediment within top 1 m; Lininger et al, 2018). In contrast, previous comparisons with NCSCD have found that the NCSCD may overestimate stocks in some areas (Zubrzycki et al, 2013).…”
Section: Carbon Stocks In the Yfmentioning
confidence: 61%
“…We sampled floodplain sediments over two field seasons (Summer 2014 and 2015) along five rivers within the YF with varying drainage areas (Text S1 in the supporting information). For further description of sampling methodology and fieldwork, see Lininger et al (2018) and supporting information Text S1. We sampled mineral sediment in increments of approximately 18 cm with an auger or a soil corer, stopping when we reached 1 m in depth or point of refusal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to carbon inputs, recent work on other floodplains in the Rocky Mountains and elsewhere suggests that autochthonous inputs dominate (Scott and Wohl, in review; Lininger et al, ). The lack of buried, high OC concentrations at depth in the soil cores from the beaver meadows suggests that autochthonous, rather than allochthonous, inputs also dominate these floodplains.…”
Section: Discussionmentioning
confidence: 99%
“…Erosion regulates the fate of OC (Doetterl et al, 2016;Hilton, 2017;Wang et al, 2017) and whether that OC is stored long-term in sedimentary sinks (Blair & Aller, 2012) or respired to the atmosphere by microbes (Falloon et al, 2011;Jobbágy & Jackson, 2000). Modeling indicates that sedimentation dynamics should regulate the age of OC in floodplain soils (Torres et al, 2017), complementary to the idea that geomorphic processes regulate OC concentrations in those soils (Lininger et al, 2018;Scott & Wohl, 2018b;Swinnen et al, 2019;Wohl, Hall, et al, 2017) and wood loads in valley bottoms (Scott & Wohl, 2018b).…”
Section: Introductionmentioning
confidence: 99%